Sales Growth Memoderasi Pengaruh Intensitas Aset Tetap dan Profitabilitas Pada Tax Avoidance - Agastya, I Kadek Dwi; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
Tax revenue in Indonesia has decreased since 2020. The decline in tax revenue in Indonesia can be caused by the implementation of tax avoidance policies. The purpose of this study is to empirically examine the effect of fixed asset intensity and profitability on tax avoidance in the food and beverage sub-sector for companies listed on the IDX in 2012–2021, which is moderated by sales growth. The sample for this study was 12 companies with 120 amateurs obtained by purposive sampling technique. The research data was processed using SPSS software and analyzed using the MRA test. The test results obtained showed that the intensity of fixed assets and profitability showed a negative effect on tax avoidance, sales growth had no effect on moderating the intensity of fixed assets on tax avoidance, and sales growth strengthened the effect of profitability on tax avoidance. Keywords: Fixed Asset Intensity; Profitability; Sales Growth; Tax avoidance